Complex distribution and velocity field of molecular gas in NGC 1316 as revealed by the Morita Array of ALMA. (14th August 2019) - Morokuma-Matsui, Kana; Serra, Paolo; Maccagni, Filippo M; For, Bi-Qing; Wang, Jing; Bekki, Kenji; Morokuma, Tomoki; Egusa, Fumi; Espada, Daniel; Miura, Rie E; Nakanishi, Kouichiro; Koribalski, Bärbel S; et al.
Abstract: We present the results of 12 CO( J = 1–0) mosaicing observations of the cD galaxy NGC 1316 at kiloparsec resolution performed with the Morita Array of the Atacama Large Millimeter/submillimeter Array (ALMA). We reveal the detailed distribution of the molecular gas in the central region for the first time: a shell structure in the northwest, a barely resolved blob in the southeast of the center, and some clumps between them. The total molecular gas mass obtained with a standard Milky Way CO-to-H2 conversion factor is (5.62 ± 0.53) × 10^8 M_, which is consistent with previous studies. The disturbed velocity field of the molecular gas suggests that the molecular gas was injected very recently (<1 Gyr) if it has an external origin, and is in the process of settling into a rotating disk. Assuming that a low-mass gas-rich galaxy has accreted, the gas-to-dust ratio and H2 -to-H i ratio are unusually low (∼28) and high (∼5.6), respectively. To explain these ratios additional processes should be taken into account, such as effective dust formation and conversion from atomic to molecular gas during the interaction. We also discuss the interaction between the nuclear jet and the molecular gas.